2016
DOI: 10.1111/epi.13500
|View full text |Cite
|
Sign up to set email alerts
|

Depression and genetic causal attribution of epilepsy in multiplex epilepsy families

Abstract: Summary Objectives Rapid advances in genetic research and increased use of genetic testing have increased the emphasis on genetic causes of epilepsy in patient encounters. Research in other disorders suggests that genetic causal attributions can influence patients’ psychological responses and coping strategies, but little is currently known about how epilepsy patients and their relatives will respond to genetic attributions of epilepsy. We investigated the possibility that depression, the most frequent psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
(61 reference statements)
1
13
0
Order By: Relevance
“…Notably, being unemployed was associated in bivariate analyses with having a higher IES score (PR = 1.4, 95% confidence interval [CI] = 1.06-1.84). We previously showed that these seizure variables were also associated with genetic attribution, 19 leading to their inclusion in our adjusted models as potential confounders. Increasing number of lifetime seizures and time since last seizure ≤ 5 years were both significantly associated with high IES score ( Table 2).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Notably, being unemployed was associated in bivariate analyses with having a higher IES score (PR = 1.4, 95% confidence interval [CI] = 1.06-1.84). We previously showed that these seizure variables were also associated with genetic attribution, 19 leading to their inclusion in our adjusted models as potential confounders. Increasing number of lifetime seizures and time since last seizure ≤ 5 years were both significantly associated with high IES score ( Table 2).…”
Section: Resultsmentioning
confidence: 97%
“…19 Similarly, one might expect that having many relatives with epilepsy could influence perceived impact of epilepsy in both affected and unaffected people through items such as "Your relationship with other close members of your family" and possibly "Your relationship with your spouse/partner," but contrary to this expectation, number of affected relatives was not associated with the IES (Table 2). 19 Similarly, one might expect that having many relatives with epilepsy could influence perceived impact of epilepsy in both affected and unaffected people through items such as "Your relationship with other close members of your family" and possibly "Your relationship with your spouse/partner," but contrary to this expectation, number of affected relatives was not associated with the IES (Table 2).…”
Section: Mean (Sd)mentioning
confidence: 97%
See 3 more Smart Citations